Sosialisasi Pemanfaatan Tenaga Surya Sebagai Sumber Energi Listrik Di Desa Ciherang Pondok, Kabupaten Bogor - Arief Suardi Nur Chairat (Sekolah Tinggi Teknik - PLN, 2020)
One of the obstacles faced in providing electricity in rural areas is renewable energy sources, especially solar energy, which potentially in all rural areas also require inexpensive costs plus a lack of knowledge about these technologies. With a variety of goodness that exists in solar energy, counseling or socialization must be given about its utilization. Ciherang Pondok Village is located on a plateau in the area of ​​Caringin District, Bogor Regency. The village is located at a strategic point, so it has enough light intensity to utilize solar power as a source of electrical energy. Extension activities are carried out by the lecture method to convey various general information about the use of solar power as a solution to the problem of electrical energy in the countryside. As a result, the knowledge of the local community increases and can apply directly independently how to use solar energy to be used as a source of electrical energy so that the availability of energy and people's access to energy are guaranteed at affordable prices in the long term while paying attention to environmental sustainability.